2007
DOI: 10.14214/sf.308
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and height development of harvested and naturally regenerated Scots pine near the timberline in North-East Finnish Lapland

Abstract: Researchers and professionals in practical forestry have faced problems concerning the regeneration success of Scots pine in natural regeneration near the timberline in North-East Lapland. The aim of the study was to analyze the seedling establishment and seedling height development of Scots pine in seed-tree stands in the area. The average number of living pine seedlings in the study stands was about 1000 ha -1 , but there was considerable variation between the stands. The seedling density was modelled using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Poor natural regeneration of Scots pine in harsh climate conditions is known to be associated with northern latitude, high elevation, and low temperature sum causing small seed crops, a low seedling establishment rate, slow height growth and high seedling mortality (Varmola et al 2004;Hyppönen et al 2005;Juntunen and Neuvonen 2006). In North-East Finland, the regeneration of Scots pine has been even more difficult than elsewhere in the timberline regions (Niemelä 2002;Hallikainen et al 2007). One reason has been assumed to be ground vegetation (Hallikainen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Poor natural regeneration of Scots pine in harsh climate conditions is known to be associated with northern latitude, high elevation, and low temperature sum causing small seed crops, a low seedling establishment rate, slow height growth and high seedling mortality (Varmola et al 2004;Hyppönen et al 2005;Juntunen and Neuvonen 2006). In North-East Finland, the regeneration of Scots pine has been even more difficult than elsewhere in the timberline regions (Niemelä 2002;Hallikainen et al 2007). One reason has been assumed to be ground vegetation (Hallikainen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Hallikainen et al (2007) Scots pine regeneration on these kinds of sites was generally slow and poor in spite of site preparation, but there was quite a variation in the results. Results of that study suggest that soil properties, field and ground layer vegetation, fungal infections, and reindeer grazing may be associated with slow and poor regeneration, but closer inspection is needed to reveal the ultimate causes.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many previous studies have shown significant relationships between the succession of natural regeneration and site factors as well as the mother stand (Tegelmark, 1998;Hille and Ouden, 2004;Hallikainen et al, 2007). More specifically, soil scarification has proved to be particularly favourable for other species of the boreal coniferous zone, such as spruce, beech and birch (Huss and Burshcel, 1972;Dohrenbusch, 1997).…”
Section: Introductionmentioning
confidence: 99%